Perencanaan Pengembangan Prasarana Kawasan Ekowisata Situ Gede Kota Bogor: Infrastructure Development Planning of Situ Gede Ecotourism Area - Muhammad Fatahudin; M Yanuar Jawardi Purwanto; Maulana Ibrahim Rau (Departemen Teknik Sipil dan Lingkungan, IPB University, 2021)
Situ Gede area includes a local protection area, functioning as a water catchment area and protected area that will be developed into an ecotourism area based on RTRW and RTBL Situ Gede area and CIFOR fiscal year 2014. The research was conducted to evaluate the existing infrastructure and to make the planning of its development special on environmental roads, waste systems, and parking buildings. The research method begins with the creation of the basic map of Situ Gede area, the retrieval of existing data using secondary data, infrastructure planning in the form of environmental roads, waste management system, and parking building planning, and the creation of infrastructure development planning map Situ Gede area as an external expected from this research. Planning to observe the conservation aspects of water resources by conducting zoning utilization. The zoning arrangement was conducted to provide protection, use, and control of existing resources, especially the creation of a lake boundary of 50 m wide from the body.